Endocrine causes of recurrent pregnancy loss in patients with post-traumatic stress disorder - I.L. Kharun; A.V. Kaminskiy (Publishing House TRILIST, 2023)
Clarification of the etiology of recurrent pregnancy loss (RPL), elucidating the reasons for the increase in repeated reproductive losses are an urgent topic that requires more detailed research attention. An analytical review was performed to effectively delineate our research field: research articles, analytical notes, clinical protocols, monographic studies, Cochrane systematic reviews with meta-analysis, data from population-based retrospective cohort studies, etc. A review of the listed literature sources and an analysis of the available data on the association between endocrine dysfunction, post-traumatic stress disorder and the risk of acute respiratory distress syndrome were performed. Research in this area will be important for understanding the mechanisms that cause RPL, for the development of effective prevention and treatment strategies aimed at improving the reproductive health of women with traumatic experience of RPL. The frequency of premature termination of pregnancy is 10-25%, the part of RPL in this segment is more than 5%. Unfortunately, there are currently no positive developments regarding the reduction of the RPL frequency. The data of modern cohort studies show the RPL causes: endocrine disorders of the reproductive system; genetic factors, erased forms of adrenal gland dysfunction; lesions of the endometrium receptor apparatus, which are clinically manifested in the luteal phase insufficiency; chronic endometritis with persistence of conditionally pathogenic microorganisms and/or viruses; cervical insufficiency; uterine malformations, intrauterine synechiae; antiphospholipid syndrome and other autoimmune disorders. Endocrine disorders such as polycystic ovary syndrome, hyperandrogenism, hyperprolactinemia, thyroid dysfunction, insulin resistance, and type 2 diabetes mellitus were analyzed to establish the association between endocrine dysfunction and RPL. The importance of a holistic approach to the diagnosis and treatment of RPL has been demonstrated. It is necessary to take into account the patient's emotional and mental state, in particular, signs of post-traumatic stress disorder, which can significantly affect the ratio of sex hormones, and ther№efore 5-6(7, can c0)/грause the eуденьxacerba 2023 WWWtion of such diseases in a w.REPRODUCT-ENDOoman as type 2 diabet.COM / es mellitusWWW, aut. oimmune thREPRODUCT-ENDOyroiditis, h.CypothOM.yrUAoidism, and others.